THE CORRELATION BETWEEN LIFESTYLE AND INCREASED URIC ACID LEVELS IN THE ELDERLY - Wijayanti, Lono; Wahyudi, Agus; Septianingrum, Yurike (Nurse and Holistic Care, 2021)
Background: Increased serum uric acid levels are the strong predictors of death due to cardiovascular damage. The sedentary lifestyle tends to make physical inactivity and less attention to nutrition in eating. There has been a lifestyle shifting, whether we realize it or not. Objective: The purpose of this study was to analyze the correlation between lifestyle and the incidence of uric acid in the elderly at nursing home (Griya Werdha) Jambangan Surabaya. Methods: This study was an analytic study with a cross-sectional approach. The population was 150 elders. A total sample was 109 respondents which taken used Simple Random Sampling.  The independent variable was lifestyle and the dependent variable was the incidence of uric acid in the elderly. The research instrument used a questionnaire and observation. This research test used Fisher's exact test = 0.05. Results: The results showed that some respondents (78.9%) experienced a bad lifestyle and some respondents (81.7%) increased uric acid. There was a correlation between lifestyle and increased of uric acid levels (p=0.000). Conclusion: The worse a person's lifestyle, the higher risk of increased uric acid levels. It is expected that the elderly able to perform a healthy lifestyle to prevent elevated uric acid levels